2015
DOI: 10.4036/iis.2015.b.03
|View full text |Cite
|
Sign up to set email alerts
|

Noxious or Non-noxious Inputs to Oxytocin Neurons: Possible Roles in the Control of Behaviors

Abstract: Oxytocin plays an essential role in milk ejection and parturition in mammals. Oxytocin has also been shown to be involved in the control of various behaviors, including anxiety-related behaviors, food intake and affiliative behaviors.We previously showed that noxious stimuli or stimuli previously paired with noxious stimuli (conditioned fear stimuli) activate hypothalamic oxytocin neurons via activation of brainstem catecholaminergic/prolactin-releasing peptide (PrRP)-positive neurons. Oxytocin neurons are act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Animal studies have shown that various physiological and psychological stressful stimuli, such as noxious stimuli [ 8 ], conditioned fear stimuli [ 9 ], social defeat stress [ 10 , 11 , 12 , 13 , 14 ], immobilization stress [ 15 ], shaker stress [ 16 ], forced swimming [ 17 , 18 ], cold stress [ 19 ], high-intensity exercise [ 20 ] and immune challenges by lipopolysaccharides [ 21 ] or interleukin-1 [ 22 ], activate oxytocin neurons and facilitate the release of oxytocin into the plasma and within the brains of mice and rats [ 23 , 24 , 25 ]. Social instability stress in adolescent female rats has been reported to decrease oxytocin immunoreactivity in the hypothalamic paraventricular nucleus [ 26 ] possibly due to oxytocin release.…”
Section: Stress Responses and Oxytocinmentioning
confidence: 99%
“…Animal studies have shown that various physiological and psychological stressful stimuli, such as noxious stimuli [ 8 ], conditioned fear stimuli [ 9 ], social defeat stress [ 10 , 11 , 12 , 13 , 14 ], immobilization stress [ 15 ], shaker stress [ 16 ], forced swimming [ 17 , 18 ], cold stress [ 19 ], high-intensity exercise [ 20 ] and immune challenges by lipopolysaccharides [ 21 ] or interleukin-1 [ 22 ], activate oxytocin neurons and facilitate the release of oxytocin into the plasma and within the brains of mice and rats [ 23 , 24 , 25 ]. Social instability stress in adolescent female rats has been reported to decrease oxytocin immunoreactivity in the hypothalamic paraventricular nucleus [ 26 ] possibly due to oxytocin release.…”
Section: Stress Responses and Oxytocinmentioning
confidence: 99%
“…9 Some stressful stimuli, including noxious stimuli, 10 conditioned fear stimuli, 11 social defeat, [12][13][14][15][16] immobilisation stress, 17 shaker stress 18 and forced swimming 19,20 , as well as administration of lipopolysaccharide 21 and interleukin-1, 22 activate oxytocin-synthesising neurones in the hypothalamus and facilitate oxytocin release into the plasma or within the brain of mice or rats. 9 Some stressful stimuli, including noxious stimuli, 10 conditioned fear stimuli, 11 social defeat, [12][13][14][15][16] immobilisation stress, 17 shaker stress 18 and forced swimming 19,20 , as well as administration of lipopolysaccharide 21 and interleukin-1, 22 activate oxytocin-synthesising neurones in the hypothalamus and facilitate oxytocin release into the plasma or within the brain of mice or rats.…”
Section: Activation Of Oxytocin Neurones After Stressful Stimulimentioning
confidence: 99%
“…Stressful stimuli induce stereotypical alarm responses, especially in the neuroendocrine system, autonomic nervous system and immune system and in behaviours, and influence health conditions in humans. 9 Some stressful stimuli, including noxious stimuli, 10 conditioned fear stimuli, 11 social defeat, [12][13][14][15][16] immobilisation stress, 17 shaker stress 18 and forced swimming 19,20 , as well as administration of lipopolysaccharide 21 and interleukin-1, 22 activate oxytocin-synthesising neurones in the hypothalamus and facilitate oxytocin release into the plasma or within the brain of mice or rats. 23,24 Exercise has also been shown to facilitate oxytocin release in horses.…”
Section: Activation Of Oxytocin Neurones After Stressful Stimulimentioning
confidence: 99%
See 1 more Smart Citation